Pengaruh Pembelajaran Multimedia Animasi Untuk Meningkatkan Kreativitas Mahasiswa Sistem Informasi Dengan Menggunakan Macromedia Flash 8 - Mhd. Aria Agung Widodoa; Ira Murni; Cindy Cintya; Ali Ikhwan (CV. ITTC INDONESIA, 2023)
Learning media is one of the components of mechanical input. Teaching and learning activities that have a significant impact on students' understanding of the history of systems, characteristics, and operations. Multimedia is a combination of different media to convey information, examples of communication media are text, images, photos, videos, music, even animation. Information systems is one of the majors that studies a system to management in making decisions and conducting business operations, and a combination of human, information technology, and organized processes.